2000
DOI: 10.1590/s0100-879x2000000900008
|View full text |Cite
|
Sign up to set email alerts
|

alpha-Globin genes: thalassemic and structural alterations in a Brazilian population

Abstract: Seven unrelated patients with hemoglobin (Hb) H disease and 27 individuals with a -chain structural alterations were studied to identify the a -globin gene mutations present in the population of Southeast Brazil. The -a 3.7 , --MED and -(a) 20.5 deletions were investigated by PCR, whereas non-deletional a -thalassemia (a Hph a , a NcoI

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 22 publications
3
29
0
1
Order By: Relevance
“…In our results, the frequency of thalassemia was lower among patients with CVD, but with no significant difference when compared to the ones without cerebrovascular involvement. Furthermore, only 15.8% had α-thalassemia compared to the reported prevalence of 20 to 25% in Afro-Brazilian population with SCA 17 . An increased HbF concentration can ameliorate SCA severity.…”
mentioning
confidence: 59%
“…In our results, the frequency of thalassemia was lower among patients with CVD, but with no significant difference when compared to the ones without cerebrovascular involvement. Furthermore, only 15.8% had α-thalassemia compared to the reported prevalence of 20 to 25% in Afro-Brazilian population with SCA 17 . An increased HbF concentration can ameliorate SCA severity.…”
mentioning
confidence: 59%
“…They are all encountered in Mediterranean populations. In Brazil, the -a 3.7 deletion has been frequently found in the Black population (10,11), and the --MED and -(a) 20.5 deletions have sporadically been described (12,13). One family with the nondeletional form a HphI a has been recently reported (13).…”
Section: Introductionmentioning
confidence: 99%
“…Although α-thalassemia is present throughout the world, its distribution varies greatly among different populations. In Brazil, most of the recognized α-thalassemia mutations involve deletions of one α-globin gene (α + -thalassemias), although several cases of α 0 -thalassemias have been reported in the literature (8)(9)(10)(11)(12). It has been shown that the -α 3.7 deletion is the most frequent mutation in the Brazilian population, occurring in 20-25% of the black population in the Southeastern region of the country (13).…”
mentioning
confidence: 99%